2015
DOI: 10.1016/j.bbamcr.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Functional and physiopathological implications of TRP channels

Abstract: Transient Receptor Potential (TRP) channel proteins are a diverse family of proteins that are expressed in many organisms, tissues and cell types. TRP channels respond to a variety of stimuli, including light, mechanical or chemical stimuli, temperature, pH or osmolarity. In addition, several TRP family members have been identified as downstream molecules in the G protein-coupled receptor signaling pathway. TRP proteins are involved in a variety of cell functions both in non-excitable and excitable cells due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 218 publications
(257 reference statements)
0
76
0
Order By: Relevance
“…TRPs are a diverse family of proteins expressed in many organisms, tissues and cell types. Their variety is demonstrated by proposed functions: transmission of painful stimuli, modulation of vascular tone, involvement in pathogenesis of diabetes mellitus, supply of intracellular calcium stores and modulation of cell cycle, [3,4]. In sensory neurons, TRPs contribute to many of activities including thermal sensation, homeostasis of body temperature and pain [5].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPs are a diverse family of proteins expressed in many organisms, tissues and cell types. Their variety is demonstrated by proposed functions: transmission of painful stimuli, modulation of vascular tone, involvement in pathogenesis of diabetes mellitus, supply of intracellular calcium stores and modulation of cell cycle, [3,4]. In sensory neurons, TRPs contribute to many of activities including thermal sensation, homeostasis of body temperature and pain [5].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In the central nervous system (CNS), they have been associated with synaptic transmission, neurogenesis and brain development [6,7]. These special nociceptive receptors are transporters of mono and bivalent cations into the cell [3]. The structure of TRPs was unknown for a long time, despite numerous crystallization attempts to resolve their structure, recently almost the entire three-dimensional structure of the vanilloid 1 (TRPV1) and ankyrin 1 (TRPA1) receptor was determined by single-particle electron cryo-microscopy [8][9][10].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…One of them is the TRP vanilloid family (TRPV), which consists of six ion channels. TRPVs modulate a variety of cellular processes including hormone secretion, cell migration as well as growth and apoptosis [1,2]. Numerous studies collectively indicated that these effects are predominantly mediated by calcium-dependent mechanisms [36].…”
Section: Introductionmentioning
confidence: 99%
“…Since these FRET biosensors are designed to sense the structural changes in proteins that organize the actin cytoskeleton for cell-cell or cell-substrate interactions, other molecules such as N-cadherin, a-catenin, integrins, paxillin, talin, and p130 Cas (67,68) can be utilized for biosensors with better sensitivity and dynamic range. Another candidate may be transient receptor potential (TRP) channel proteins, which respond to a variety of stimuli, including mechanical or chemical stimuli, temperature, or osmolarity (69). After selecting the most appropriate protein, it is necessary to optimize the FPs for deep tissue imaging, as discussed above.…”
Section: Visualization Of Physical Stresses In Vivomentioning
confidence: 99%